Boundedness for some Schrödinger Type Operators on Weighted Morrey Spaces. (30th January 2014) - Pan, Guixia; Tang, Lin
Abstract : We establish the boundedness of some Schrödinger type operators on weighted Morrey spaces related to certain nonnegative potentials belonging to the reverse Hölder class.